PELESTARIAN DAN PUBLIKASI VISUAL BANGUNAN BERSEJARAH BOYOLALI MASA KOLONIAL MELALUI MEDIA DIGITAL - Alam, M. Bagus Sekar; Warto, Warto; Widi Wardojo, Waskito; Kusuma Hastuti, Tiwuk; Yuliati, Umi; Febriary Setiasih, Insiwi; Juwono, Harto (Universitas Mataram, 2025)
Siswodipuran Subdistrict, located in Boyolali Regency, Central Java, is home to a number of historical colonial-era buildings that have yet to be systematically documented. A lack of public and governmental awareness and understanding regarding the historical value and economic potential of these heritage structures poses a significant challenge. This community engagement program aims to support the preservation and visual dissemination of these colonial buildings through digital media as a means of education, research, and strengthening local identity. The methods employed include lectures, discussions, guided historical scriptwriting, documentary video production, and online publication. The Social History Research Group of the Faculty of Cultural Sciences, Universitas Sebelas Maret, in collaboration with community partners and the local government, produced a documentary video and media publications highlighting the historical potential of the Siswodipuran area. The outcomes of this program include popular articles, educational videos on YouTube, and increased community participation in cultural heritage preservation. It is expected that this initiative can serve as a model for local historical documentation and encourage the utilization of historical buildings as cultural and economic assets for the community.